2017
DOI: 10.1136/gutjnl-2017-314828
|View full text |Cite
|
Sign up to set email alerts
|

Resection of pancreatic cancer in Europe and USA: an international large-scale study highlighting large variations

Abstract: Rates of PaC resection remain low in Europe and USA with great international variations. Further studies are warranted to explore reasons for these variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(139 citation statements)
references
References 47 publications
3
131
2
3
Order By: Relevance
“…The resection rate in our study was 17.2%, which is comparable to the rate in the Netherlands (17.9%) and higher than that in Norway (13%) [23]. The overall resection rate of PC in Denmark increased from 12.0%-17.6% from 2011-2012 to 2013-2014 [23]. Four centers in Denmark perform PC resections, with an annual volume of 13-82 patients.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The resection rate in our study was 17.2%, which is comparable to the rate in the Netherlands (17.9%) and higher than that in Norway (13%) [23]. The overall resection rate of PC in Denmark increased from 12.0%-17.6% from 2011-2012 to 2013-2014 [23]. Four centers in Denmark perform PC resections, with an annual volume of 13-82 patients.…”
Section: Discussionsupporting
confidence: 63%
“…In this nationwide, population-based study, 623 patients underwent curative intent resection for ductal adenocarcinoma of the pancreas between 2011 and 2016. The resection rate in our study was 17.2%, which is comparable to the rate in the Netherlands (17.9%) and higher than that in Norway (13%) [23]. The overall resection rate of PC in Denmark increased from 12.0%-17.6% from 2011-2012 to 2013-2014 [23].…”
Section: Discussionsupporting
confidence: 59%
“…Although the TNM staging system is not directly translatable to widely used resectability criteria, 5 the low resection rate in this study, compared with that previously reported, 20 is noteworthy and could be explained by the inclusion of patients C 70 years of age. In addition, some patients may have anatomically resectable disease, yet have unfavorable biological (high CA19.9) and conditional (poor functional status) factors.…”
Section: Discussioncontrasting
confidence: 57%
“…Approximately 50% of patients with PDAC are classified as having clinically localized disease, with locally advanced disease diagnosed in about 35% [8]. Therefore, those classified as having resectable disease account for fewer than 20% of patients with newly diagnosed PDAC [9]. When PDAC is suspected based on blood pancreatic enzyme levels, tumor markers, and ultrasonography, contrast-enhanced multidetector row computed tomography (MDCT) is useful for defining the diagnosis and resectability because of its excellent resolution, widespread availability, and cost.…”
Section: Definition Of R/br and Diagnostic Modalitiesmentioning
confidence: 99%